Analisis Pengaruh Inflasi, Pengangguran Dan Belanja Pemerintah Terhadap Kemiskinan di Sumatera Utara Tahun 1991-2020 - Nadeak, Royan Abel (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the effect of inflation, unemployment and government spending on poverty in North Sumatra in 1991-2020. This study uses time series data obtained from the Central Statistics Agency of North Sumatra. This study uses the Error Correction Model (ECM) analysis method. To determine the effect of the independent variable on the dependent variable in the short term and Multiple Linear Regression to determine the effect of the independent variable on the dependent in the long term. From the results of the ECM estimation or short-term analysis, it shows that only the inflation variable has a significant and positive effect on the poverty level in North Sumatra. In the long term, the unemployment variable has been shown to have a significant and positive effect on poverty. On the other hand, in the short term it is also proven that changes in unemployment have a significant and positive effect on poverty. In the long term, the variable of government expenditure has been shown to have a significant and negative effect on poverty.